2007
DOI: 10.1161/circulationaha.107.696294
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Preexcitation Modulates Strain and Attenuates Cardiac Remodeling in a Swine Model of Myocardial Infarction

Abstract: Background-Myocardial infarction modifies the distribution of stress within the heart, increasing wall stress in ischemic and surrounding tissue, which often leads to adverse left ventricular remodeling. Electrical preexcitation pacing with appropriate timing of high-stress regions can reduce local strain and may attenuate global remodeling. Methods and Results-Myocardial infarction was induced in 24 swine to study the short-term (nϭ12) and long-term (nϭ12) effects of therapy. Sonomicrometry and hemodynamic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…However, at A-V delays of 50% or greater of the P-R interval, stroke work and cardiac output were similar to values without early electrical activation. Consistent with the findings of Shuros et al (18), cardiac output and developed LV pressures at the A-V delay used in the present study were not altered during the period of early electrical activation. A potential explanation of this finding is that with A-V delays that are close to the intrinsic P-R interval, the spread of depolarization in the region of myocardium that is activated early is relatively small and that LV pressure development is driven by depolarization of the LV through the normal HisPurkinje system.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, at A-V delays of 50% or greater of the P-R interval, stroke work and cardiac output were similar to values without early electrical activation. Consistent with the findings of Shuros et al (18), cardiac output and developed LV pressures at the A-V delay used in the present study were not altered during the period of early electrical activation. A potential explanation of this finding is that with A-V delays that are close to the intrinsic P-R interval, the spread of depolarization in the region of myocardium that is activated early is relatively small and that LV pressure development is driven by depolarization of the LV through the normal HisPurkinje system.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the A-V delay for the early activation LV site was set at 80 ms, which was ϳ75% of the intrinsic P-R delay when the atria were stimulated at a rate of 150 beats/min. Shuros et al (18), in the context of inducing early electrical activation of the border region of a myocardial infarct (MI), demonstrated that the reduction in regional strain with early electrical activation was inversely related to the A-V delay relative to the intrinsic P-R interval. Specifically, at an A-V delay of 10% of the intrinsic P-R interval, Shuros et al (18) observed a significant reduction in the shortening (i.e., strain) in the early activation region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this AV delay provides maximum benefit is unknown; however, preliminary animal studies suggest that pacing continuously at an AV delay of 60% to 75% from sites near the infarcted region is effective in attenuating adverse ventricular remodeling. 21 The optimal timing of initiating biventricular therapy following an MI has not been established and will likely have an impact on outcomes.…”
Section: Discussionmentioning
confidence: 99%